A review of the current status and pathways of cost control in Small and Medium-sized Catering Enterprises: From a lean management perspective - Tao, Xin; Lee, Khai Loon (Journal of Islamic, Social, Economics and Development, 2025)
As China’s catering industry experiences steady expansion, small and medium-sized enterprises (SMEs) play a vital role in market diversification and job creation. Yet, these businesses are increasingly challenged by volatile raw material costs, rising labor expenses, and competitive pressures. Effective cost control has become essential to their continued growth. Many SMEs still rely on traditional, experience-based cost practices, which are insufficient in today's complex market landscape. Lean management, emphasizing waste reduction and continuous improvement, has shown strong potential in service sectors beyond its manufacturing origins. This review draws on lean principles to examine recent studies—both chinese and international—on cost control strategies in catering SMEs. It discusses the evolution of management approaches, identifies common implementation challenges, and highlights areas where current research falls short. The paper further evaluates how lean management can be practically integrated into real-world catering operations. By doing so, it aims to support SMEs in strengthening cost efficiency and long-term sustainability.